Appling A Hybrid Encryption Algorithm in Cloud Computing‎ - Esraa Alobaydi; Muna Jawhar (Al-Rafidain Journal of Computer Sciences and Mathematics)
The rapid digital development has led to a steady increase in the use of cloud storage as a ‌primary means of saving and sharing data and files. This development brought major ‌challenges in the field of security and data protection, as well as the concerns related to hacking and ‌information theft are constantly escalating. Hence, the importance of applying strong encryption ‌techniques to protect data saved in cloud storage. For this reason, this study explores and ‌presents an advanced encryption strategy that combines three of the most powerful known ‌algorithms which are Blowfish, Paillier, and AES with the aim of increasing the level of security and ‌privacy during uploading files to the cloud storage. This research aims to provide an overview of how ‌this process can be implemented using these nested hybrid algorithms and the potential benefits ‌of this multi-layered approach. While these algorithms are diverse, effective, and strong in protection, ‌which yields the contribution significantly to increasing the level of security in the field of storing ‌sensitive data in the cloud. The obtained results showed that the hybrid algorithm gives the ability to combine different advantages of the encryption algorithms and achieve the ideal balance between strong protection and efficient performance in the field of in-cloud data protection with minimal time consumption.